Working with fathers of at-risk children: Insights from a qualitative process evaluation of an intensive group-based intervention. (October 2016) - Scourfield, Jonathan; Allely, Clare; Coffey, Amanda; Yates, Peter
Abstract: This article is based on qualitative research with fathers who attended Mellow Dads, an intensive 'dads only' group-based intervention underpinned by attachment theory for fathers of at-risk children. Specifically the article draws on data from a process evaluation of the programme in order to explore the challenges of engaging men in effective family work. The methods used to undertake the process evaluation included participant observation of one complete Mellow Dads course, interviews with fathers and facilitators, interviews with the intervention author and a study of programme documentation. The article focuses on the theoretical underpinning of the programme, its acceptability to the fathers and the challenges faced by facilitators in delivering the programme as intended. The fathers appreciated the efforts of facilitators to make the group work, valued the advice on play and parenting style as well as the opportunity to meet other fathers in similar circumstances. However, there were obstacles that impacted on the effectiveness of the programme. These included the considerable time required to get the men to attend in the first place and then to keep them coming, the lack of practice of parenting skills when fathers were not living with their children, and the difficulties of sharing personal information. The challenges identified raise questions about how much change can be expected from vulnerable fathers and whether programmes designed for mothers can be applied to fathers with little adaptation. The article aims to contribute to ongoing dialogue about the best way to successfully engage fathers in children's well-being, and raises the question as to whether working with fathers requires different skill-sets and approaches from the more familiar social work territory of working with mothers. Highlights: This is a rare example of an in-depth qualitative study of a parenting programme for fathers. The study includes direct observation of how programme is put into practice and the views of fathers and practitioners The paper highlights the practitioners' skilful building of relationships with the fathers The paper addresses the question of whether working with fathers is distinct from working with mothers The authors recommend that expectations of change may need to be modest when working with the fathers of at-risk children.